Dual fluorescence system for analysis of transcriptional response in multi-species planktonic and biofilm context - Miao, Huang (2009)
Bacteria found in various ecosystems are often multi-species in context and the interspecies interactions are likely to lead to complex intracellular changes not observed in single-species cultures. Here we describe a dual fluorescence system that allows analysis of transcriptional responses of Escherichia coli as influenced by other species. We used two other species reported to be members of the intestinal microbiota of neonates in addition to E. coli: Klebsiella pneumoniae and Enterococcus faecalis. Multi-species co-culture condition was established. E. coli strain MG1655 was genetically manipulated to generate strain SCC1, which constitutively expresses green fluorescent protein. Plasmids carrying promoters of interest, fused to a red fluorescent protein gene (AsRed2), were introduced into strain SCC1. When a co-culture of E. coli strain SCC1 carrying promoter-AsRed2 fusion and a non-E. coli strain was analyzed by FACS, it enabled (i) distinction of E. coli SCC1 from the non-E. coli strain, (ii) analysis of the E. coli promoter activity via AsRed2 expression and (iii) identification of transcriptional heterogeneity within the E. coli population. Spatial distribution of promoter activities in biofilm co-cultures can also be visualized via CLSM. This system has revealed that E. coli fadB and rpoE transcription were differentially influenced by the partner species under various growth conditions. Exploration to develop this established system further is presented and discussed. This is the first analysis system reported to date to allow transcriptional response due to bacterial interspecies interactions to be studied, even when the species to be analyzed is a severe minority.